Negative electrode for rechargeable battery and rechargeable battery comprising the same

CN123017879APending Publication Date: 2026-10-30SAMSUNG SDI CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610545664.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-28
Filing Date
2026-04-23
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

[0009]尽管不具有常规集流体,但是根据本公开的实施例的用于可再充电电池的负电极板可以具有薄的厚度、高的能量密度和长的循环寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017879A_ABST
    Figure CN123017879A_ABST
Patent Text Reader

Abstract

A negative electrode for a rechargeable battery and a rechargeable battery including the same are provided. The negative electrode for a rechargeable battery is formed of a layer including a network of graphite nanofibers. The layer has a specific surface area of 7 m 2 / g or more and a porosity of 75% to 90%.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims priority and benefit to Korean Patent Application No. 10-2025-0055067, filed on April 28, 2025, with the Korean Intellectual Property Office, the entire disclosure of which is incorporated herein by reference. Technical Field

[0002] This disclosure relates to a negative electrode for a rechargeable battery and a rechargeable battery including the negative electrode. Background Technology

[0003] With the proliferation of battery-powered electronic devices (such as mobile phones, laptops, and electric vehicles), the demand for rechargeable batteries with high energy density and capacity has increased. Therefore, there is a growing expectation to improve the performance of rechargeable lithium-ion batteries.

[0004] Rechargeable lithium batteries typically include a positive electrode and a negative electrode containing active materials capable of inserting and deintercalating lithium ions. Rechargeable lithium batteries generate electrical energy through oxidation and reduction reactions as lithium ions are deintercalated from the negative electrode and inserted into the positive electrode, and vice versa. Summary of the Invention

[0005] This disclosure aims to provide a negative electrode for a rechargeable battery that provides high energy density and long cycle life without conventional current collectors.

[0006] This disclosure also aims to provide a rechargeable battery including the negative electrode.

[0007] According to one embodiment, the negative electrode for a rechargeable battery is formed of a layer comprising a network of graphite nanofibers, wherein the layer has a 7m² depth. 2 / g or greater specific surface area and 75% to 90% porosity.

[0008] Another embodiment provides a rechargeable battery including a negative electrode for the rechargeable battery and a positive electrode.

[0009] Although it does not have a conventional current collector, the negative electrode plate for a rechargeable battery according to embodiments of the present disclosure can have a thin thickness, high energy density and long cycle life. Attached Figure Description

[0010] The above and other objects, features and advantages of the present invention will become more apparent to those skilled in the art from the detailed description of exemplary embodiments of the invention with reference to the accompanying drawings.

[0011] Figure 1 This is a cross-sectional view of the negative electrode for a rechargeable battery according to an embodiment.

[0012] Figure 2 This is a cross-sectional view of an assembly of a negative electrode plate, a separator, and a positive electrode plate for a rechargeable lithium battery according to an embodiment of the present disclosure.

[0013] Figures 3 to 6 This is a cross-sectional view of a rechargeable lithium battery according to an embodiment of the present disclosure.

[0014] Figure 7 SEM (scanning electron microscope) images of the surface of a negative electrode for a rechargeable battery according to embodiments of the present disclosure are shown.

[0015] Figure 8 A TEM (transmission electron microscope) image of the crystalline state of graphite fibers in the negative electrode of a rechargeable battery according to an embodiment of the present disclosure is shown.

[0016] Figure 9 The XRD (x-ray diffraction) analysis results for Example 1 are shown. Detailed Implementation

[0017] Example embodiments of the present disclosure are described in detail below. However, these are presented by way of example, and the present disclosure is not limited to the explicitly disclosed examples.

[0018] Unless otherwise stated herein, when a component such as a layer, film, region, or plate is described as being “on” another component, this includes not only the case where the component is “directly on” the other component, but also the case where there is another component between them.

[0019] Unless otherwise stated, a singular expression may also include a plural expression. Furthermore, unless otherwise stated, “A or B” may mean “including A, including B, or including both A and B”.

[0020] In the specification, “the combination of them” can mean mixtures of components, laminates, complexes, copolymers, alloys, blends and reaction products.

[0021] In this specification, "particle size (D50)" refers to the average particle size representing the size of particles that constitute 50% of the cumulative volume in a particle size distribution. The particle size distribution can be measured using methods well-known to those skilled in the art. For example, it can be measured using a particle size analyzer or by transmission electron microscopy or scanning electron microscopy. Alternatively, by using a measuring device utilizing dynamic light scattering, particle size can be measured using dynamic light scattering. The number of particles in each particle size range can be counted through data analysis, and the D50 value can be calculated using the methods described above. Optionally, the number of particles can be measured using laser diffraction. When measured by laser diffraction, for example, the particles to be measured can be dispersed in a dispersion medium and irradiated with ultrasound at approximately 28 kHz at a 60 W output using a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000). The D50 can then be calculated using the measuring device based on 50% of the particle size distribution.

[0022] If the particles are spherical, then the above dimensions could mean the diameter.

[0023] The negative electrode for a rechargeable battery according to an embodiment does not include the current collector included in conventional negative electrodes. Instead, the negative electrode according to this disclosure includes a layer comprising a network of graphite nanofibers (hereinafter simply referred to as "graphite nanofiber network") capable of serving as both a current collector and an active material layer.

[0024] As used herein, the term "current collector" refers to a plate on which an active material layer is formed, and is formed, for example, of copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.

[0025] The negative electrode for a rechargeable battery according to embodiments of this disclosure consists of a layer comprising a graphite nanofiber network. That is, the negative electrode for a rechargeable battery can be simply a layer comprising a graphite nanofiber network (consisting only of a layer comprising a graphite nanofiber network), thereby having a thin thickness and improving battery capacity.

[0026] Graphite nanofibers are one-dimensional fibers. The aforementioned layer has a porous structure formed by graphite nanofibers entangled in a network structure. This layer is a porous structure formed by graphite nanofibers entangled in a network structure. Graphite nanofibers are prepared by graphitizing nanofibers through electrospinning or the like. Here, graphitization refers to heat-treating the nanofibers to give them (002) crystal planes, which are characteristic of conventional graphite, exhibiting an XRD peak at 2θ = 26° and having a crystal plane spacing of 3.35 Å as confirmed by TEM. Using this disclosure, when a layer containing graphite nanofibers is prepared by graphitization, the layer can be used as both a current collector and an active material layer having specific surface area and porosity.

[0027] The layer containing the graphite nanofiber network has a thickness of 7m. 2 / g or greater specific surface area and 75% to 90% porosity. When the specific surface area of ​​the layer containing the graphite nanofiber network is less than 7m². 2 At a porosity of 75% to 90%, the movement of lithium ions and electrons may be hindered, which could reduce the energy density of the battery. When the porosity of the layer containing the graphite nanofiber network is 75% to 90%, with graphite fibers as the active material, the layer has the form of three-dimensional nanofibers, thus exhibiting high reactivity with lithium ions and high compression density during electrode plate rolling in battery manufacturing.

[0028] In a specific embodiment, the specific surface area (in m²) 2 The porosity (per g) can be 7, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 8, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9, 9, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9, 10, or 7 to 10. The porosity (%) can be 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 80 to 90, 85 to 90, or 87 to 90.

[0029] As used herein, “specific surface area” refers to the BET (Brunauer, Emmett, Teller) specific surface area, which can be measured by conventional methods known to those skilled in the art. BET surface area can be determined by degassing the sample, adsorption / desorption of liquid nitrogen, and by calculating data from adsorption and desorption plots using the BET equation.

[0030] As used herein, "porosity" refers to the percentage of pore area relative to the total area of ​​the layer containing the graphite nanofiber network. Porosity can be assessed using scanning electron microscopy (SEM) images with ImageJ software. Specifically, porosity is measured by the following methods: (1) Coat a layer containing a graphite nanofiber network with Pt and take at least seven SEM images of it at the same magnification; (2) Import the SEM image into the ImageJ program; (3) After specifying the area to be used to measure porosity, click “Confirm”; (4) In the Analysis tab, check the area and area fraction, and then click "Confirm"; and (5) When a specific area is selected and “Measure” is pressed, the program calculates the ratio of the pore area to the total area of ​​the layer containing the graphite nanofiber network. Here, the black area represents the pores.

[0031] According to embodiments, the layer comprising the graphite nanofiber network can be a felt. Here, "felt" refers to a graphite nanofiber network with increased packing density. The felt-like layer can prevent the layer from expanding during battery operation, thereby extending the battery's cycle life. Increasing the packing density can be achieved by increasing the concentration of the electrospinning solution during the electrospinning process, or by graphitizing and then compressing the nanofibers produced by electrospinning. However, this disclosure is not limited to these methods.

[0032] According to an embodiment, the graphite nanofibers in the layer comprising the graphite nanofiber network may themselves comprise carbon atoms having carbon-carbon covalent bonds. For example, the graphite nanofibers in the layer comprising the graphite nanofiber network can be connected to adjacent graphite nanofibers via carbon-carbon bonds. The graphite nanofibers can entangle with each other to form a felt.

[0033] Graphite nanofibers can have an average diameter of 200 nm to 600 nm. Within this range, graphite nanofibers can readily possess the aforementioned specific surface area, porosity, and flexibility, thus enabling their use in applications such as core-type negative electrodes. For example, the average diameter (in nm) of graphite nanofibers can be 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 400, 410, 420, 430, 440, 450, 460, 470, 480, 490, 500, 510, 520, 530, 540, 550, 560, 570, 580, 590, 600, or 300 to 500 nm. Here, average diameter refers to the average diameter of graphite nanofibers.

[0034] The thickness (in μm) of the layer containing the graphite nanofiber network can be 10 or greater, for example, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, or 10 to 60. Within these ranges, the layer is suitable for use in batteries.

[0035] According to the examples, the graphite nanofibers exhibit a crystal plane spacing of 3.35 Å as determined using transmission electron microscopy (TEM).

[0036] In an embodiment, based on a 100 wt% layer comprising a graphite nanofiber network, the layer comprising a graphite nanofiber network may include 99.5 wt% or more, or 99.9 wt% or more, graphite nanofibers, for example, 99.9 wt% to 100 wt% or 100 wt% graphite nanofibers. Within these ranges, the battery capacity is not reduced, and the layer can serve as both a current collector and an active material layer.

[0037] Based on a 100 wt% layer comprising a graphite nanofiber network, the layer comprising the graphite nanofiber network may include 1 wt% or less (e.g., 0 wt% to 1 wt% or 0 wt% to 0.1 wt%) of one or more of a binder and a conductive material. Here, the binder and conductive material may be those commonly used in the negative electrode of a rechargeable battery.

[0038] Hereinafter, a method for manufacturing a negative electrode for a rechargeable battery according to an embodiment will be described.

[0039] The negative electrode for a rechargeable battery can be manufactured by the following steps: preparing an electrospinning solution containing a carbon-containing polymer; electrospinning the electrospinning solution on a substrate to form a polymer nanofiber network; and graphitizing the polymer nanofiber network and removing the substrate.

[0040] Carbon-containing polymers are not limited, as long as they are capable of electrospinning. Polymers may include, for example, polyacrylonitrile (PAN), polyimide, or polyacrylate, but this disclosure is not limited to these examples. Preferably, the polymer may be polyacrylonitrile.

[0041] The electrospinning solution may also include a solvent to promote the dispersion and dissolution of the polymer. The solvent may be dimethylformamide, dimethylacetamide, dimethyl sulfoxide, or N-methyl-2-pyrrolidone. However, this disclosure is not limited to these examples. To further enhance dispersion and dissolution, stirring and / or heat treatment may be performed.

[0042] Electrospinning can be carried out in an environment with an internal temperature of 25°C or higher (e.g., 25°C to 60°C). Within this range, the solvent in the electrospinning solution is highly volatile, resulting in no residual solvent and thus reducing the impact of solvent on the battery.

[0043] Electrospinning can be performed through the following steps: positioning a nozzle assembly and a collecting roller at intervals, the nozzle assembly including a tip with a needle size of 23G to 30G; adding an electrospinning solution to the tip; positioning a substrate on the collecting roller; and applying a voltage of 35kV to 90kV to the tip. The distance between the nozzle assembly and the active material layer can be 10cm to 20cm. When the needle size of the tip is 25G to 30G, nanofibers in a desired form suitable for electrospinning can be formed.

[0044] During the electrospinning process, the electrospinning solution is spun and stretched into fibers, thereby forming a layer comprising nanofibers on a substrate. The electrospinning solution is suspended as droplets at the tip of a nozzle due to surface tension. When a voltage is applied to the tip, charges accumulate on the solution surface, generating repulsive forces between the charges. When the repulsive forces between the charges exceed a critical voltage equal to the surface tension of the solution, a conical Taylor cone is formed. From its apex, a stream of electrospinning solution is ejected and highly elongated to form nanofibers, which are then collected on the substrate to form a fiber layer.

[0045] The nozzle pressure can be 1 MPa or higher. Within this range, the high degree of solvent evaporation reduces the impact of residual solvent on the battery.

[0046] It may be desirable to properly regulate the tip air to reduce interference between tips and ensure uniform electrospinning. The tip air can be regulated by flowing compressed air at a pressure of 0.1 MPa to 0.3 MPa.

[0047] The speed of the collecting roller can be adjusted to form a fiber layer of suitable thickness. The roller speed can be, for example, from 1 m / min to 3 m / min. The flow rate of the electrospinning solution discharged from the tip can be adjusted to a range of 20 μL / min to 200 μL / min. In an embodiment, a drying process can be performed at 60°C to 120°C after the electrospinning process.

[0048] Graphitization can be achieved by heat-treating nanofibers produced by electrospinning at temperatures between 2800°C and 3000°C. When the heat treatment temperature is below 2800°C, it may be difficult to ensure high crystallinity. Furthermore, according to XRD analysis, the (002) crystal plane may not appear at 2θ = 26°, making it difficult to achieve the aforementioned specific surface area and high carbon purity of 99.9% or greater. When the heat treatment temperature exceeds 3000°C, the temperature is too high, making it difficult to achieve the aforementioned porosity. In some examples, the heat treatment temperature can be between 2800°C and 2900°C.

[0049] Graphitization can be performed by heat treatment of nanofibers produced by electrospinning in a nitrogen atmosphere, an argon atmosphere, a hydrogen atmosphere, or a combination thereof.

[0050] Graphitization may include heat treatment of nanofibers prepared by electrospinning for 1 hour or more (e.g., 1 hour to 24 hours).

[0051] Before graphitization, nanofibers can undergo oxidative stabilization and carbonization processes.

[0052] Oxidative stabilization can remove impurities (such as nitrogen) from the polymer (e.g., polyacrylonitrile) to be electrospun prior to the carbonization process. The oxidative stabilization process may include heat-treating the electrospun polymer fiber mat by heating at a rate of 5°C / min in an oxygen atmosphere up to a final temperature of 250°C, and then holding it for 3 hours.

[0053] Carbonization is used to carbonize oxidically stabilized nanofibers. The carbonization process may involve heat-treating the nanofibers under an argon atmosphere at a heating rate of 5°C / min up to a final temperature of 1000°C, followed by holding for 3 hours.

[0054] Figure 1 This is a cross-sectional view of a negative electrode for a rechargeable battery according to an embodiment of the present disclosure.

[0055] Reference Figure 1 The negative electrode for a rechargeable battery can be formed from a layer 20 having a graphite nanofiber network, without a current collector. Here, layer 20 comprises a network of entangled graphite nanofibers.

[0056] An electrode assembly for a rechargeable battery according to one embodiment will now be described.

[0057] An electrode assembly for a rechargeable battery may include a negative electrode for the rechargeable battery. The electrode assembly may also include a positive electrode for the rechargeable battery formed on the negative electrode for the rechargeable battery.

[0058] The positive electrode for a rechargeable battery may include a current collector and a layer of positive electrode active material on the current collector. The positive electrode active material layer may include positive electrode active material and may also include a binder and / or a conductive material. The positive electrode may also include additives that can be used as a sacrificial positive electrode.

[0059] Based on a 100wt% positive electrode active material layer, the amount of positive electrode active material can be from about 90wt% to about 99.5wt%. Based on a 100wt% positive electrode active material layer, the amounts of binder and conductive material can be from about 0wt% to about 5wt%, for example, from 0.5wt% to about 5wt%.

[0060] The positive electrode active material may include compounds capable of intercalating and deintercalating lithium (lithium-intercalating compounds). Specifically, at least one of the composite oxides of lithium and metals selected from cobalt, manganese, nickel, and combinations thereof may be used.

[0061] The composite oxide can be a lithium transition metal composite oxide. Specific examples of composite oxides include lithium nickel oxides, lithium cobalt oxides, lithium manganese oxides, lithium iron phosphate compounds, cobalt-free lithium nickel manganese oxides, or combinations thereof.

[0062] As a specific example, the following compounds, represented by any of the following chemical formulas, can be used. Li a A 1- b X b O 2-c D c (0.90≤a≤1.8, 0≤b≤0.5, and 0≤c≤0.05); Li a Mn 2-b X b O 4-c D c (0.90≤a≤1.8, 0≤b≤0.5, and 0≤c≤0.05); Li a Ni 1-b-c Co b X c O 2-α D α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5, and 0<α<2); Li a Ni 1-b-c Mn b X c O 2-α D α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5, and 0<α<2); Li a Ni b Co c L 1 d G e O2 (0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, and 0≤e≤0.1); Li a NiG b O2 (0.90≤a≤1.8, and 0.001≤b≤0.1); Li a CoG b O2 (0.90≤a≤1.8, and 0.001≤b≤0.1); Li a Mn 1-b G bO2 (0.90≤a≤1.8, and 0.001≤b≤0.1); Li a Mn2G b O4 (0.90≤a≤1.8, and 0.001≤b≤0.1); Li a Mn 1-g G g PO4 (0.90 ≤ a ≤ 1.8, and 0 ≤ g ≤ 0.5); Li (3-f) Fe2(PO4)3 (0≤f≤2); or Li a FePO4 (0.90≤a≤1.8). In these chemical formulas, A is Ni, Co, Mn or a combination thereof; X is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, rare earth elements or a combination thereof; D is O, F, S, P or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof; and L 1 It is Mn, Al, or a combination thereof.

[0063] The positive electrode active material can be a nickel-based positive electrode active material (e.g., a high-nickel positive electrode active material). For example, based on 100 mol% of metals other than lithium in a lithium transition metal complex oxide, the positive electrode active material can have a nickel content of greater than or equal to about 80 mol%, greater than or equal to about 85 mol%, greater than or equal to about 90 mol%, greater than or equal to about 91 mol%, or greater than or equal to about 94 mol% and less than or equal to about 99 mol%. High-nickel positive electrode active materials can provide high capacity and can be used in high-capacity, high-density rechargeable batteries.

[0064] The binder is used to adhere the positive electrode active material particles to each other, and also to adhere the positive electrode active material to the current collector. As a non-limiting example, examples of binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers including ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylate resin, polyester resin, nylon, etc.

[0065] Conductive materials can be used to impart conductivity (e.g., electrical conductivity) to electrodes. Any material that does not cause undesirable chemical changes in a rechargeable battery and conducts electrons can be used in a battery. Examples of conductive materials include: carbon-based materials such as natural graphite, synthetic graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metallic materials, including copper, nickel, aluminum, silver, etc., in the form of metal powders or metal fibers; conductive polymers, such as polyphenylene derivatives; or mixtures thereof.

[0066] Aluminum can be used as a current collector. However, this disclosure is not limited thereto.

[0067] Depending on the type of rechargeable battery, a separator may be present between the positive and negative electrodes.

[0068] diaphragm The membrane may include polyethylene, polypropylene, polyvinylidene fluoride, or multilayer membranes of two or more layers thereof, such as mixed multilayer membranes such as polyethylene / polypropylene double membranes, polyethylene / polypropylene / polyethylene triple membranes, polypropylene / polyethylene / polypropylene triple membranes, etc.

[0069] The diaphragm may include a porous substrate and a coating on one or both surfaces of the porous substrate, comprising organic materials, inorganic materials, or combinations thereof.

[0070] The porous substrate can be a polymer film formed from any one of the following polymers or copolymers or mixtures thereof: polyolefins (such as polyethylene and polypropylene), polyesters (such as polyethylene terephthalate and polybutylene terephthalate), polyacetal, polyamide, polyimide, polycarbonate, polyetherketone, polyaryletherketone, polyetherimide, polyamideimide, polybenzimidazole, polyethersulfone, polyphenylene ether, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fiber, and polytetrafluoroethylene (such as TEFLON). ® ).

[0071] Organic materials may include polymers such as polyvinylidene fluoride or (meth)acrylic acid polymers.

[0072] Inorganic materials may include inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof. However, this disclosure is not limited to these examples.

[0073] Organic and inorganic materials can be mixed in a single coating. In other embodiments, coatings comprising organic materials and coatings comprising inorganic materials can be stacked.

[0074] Figure 2 This is a cross-sectional view of an electrode assembly for a rechargeable battery according to an embodiment of the present disclosure. (Refer to...) Figure 2 The electrode assembly for a rechargeable battery may include a negative electrode 20, a positive electrode 10, and a separator 30 located between the negative electrode 20 and the positive electrode 10. The positive electrode 10 may include a current collector 10A and a positive electrode active material layer 10B.

[0075] A rechargeable battery includes a negative electrode and a positive electrode for rechargeable batteries. A rechargeable battery may also include a separator and an electrolyte.

[0076] Electrolyte solution Electrolyte solutions may include non-aqueous organic solvents and lithium salts.

[0077] Non-aqueous organic solvents can serve as media for transporting ions that participate in the electrochemical reactions of a battery.

[0078] Non-aqueous organic solvents may be or include at least one of carbonate solvents, ester solvents, ether solvents, ketone solvents, alcohol solvents, aprotic solvents, or combinations thereof.

[0079] Carbonate solvents may include at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), and butyl carbonate (BC). For example, non-aqueous organic solvents may include a mixture comprising ethylene carbonate, methyl ethyl carbonate, and dimethyl carbonate in a volume ratio of 10 to 30:20 to 50:20 to 50.

[0080] Ester solvents may include at least one of the following: methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, caprolactone, etc.

[0081] Ether solvents may include at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. Additionally, ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc. Aprotic solvents may include at least one of the following: nitriles, such as R-CN (wherein R is a C2 to C20 straight-chain, branched, or cyclic hydrocarbon group, and may include double bonds, aromatic rings, or ether bonds, etc.); amides, such as dimethylformamide; dioxolane, such as 1,3-dioxolane, 1,4-dioxolane, etc.; sulfolane; etc.

[0082] Non-aqueous organic solvents can be used alone or in combination of two or more solvents.

[0083] In addition, when using carbonate solvents, cyclic carbonates and chain carbonates can be mixed together, and the cyclic carbonates and chain carbonates can be mixed in a volume ratio ranging from about 1:1 to about 1:9.

[0084] Lithium salts dissolved in organic solvents supply lithium ions in batteries, enabling rechargeable batteries to operate and improving lithium ion transport between the positive and negative electrodes. Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide, LiFSI), LiC4F9SO3, and LiN(C x F 2x+1 SO2)(C y F 2y+1 Lithium trifluoromethane sulfonate (where x and y are integers in the range of 1 to 20), lithium tetrafluoroethane sulfonate, lithium difluoro(oxalate)borate (LiDFOB), lithium difluorobis(oxalate)phosphate (LiDFBOP), and lithium bis(oxalate)borate (LiBOB).

[0085] Rechargeable batteries can be cylindrical, prismatic, pouch-shaped, or coin-shaped, depending on their shape.

[0086] Figures 3 to 6 This is a schematic diagram illustrating a rechargeable battery according to an embodiment of the present disclosure. Figure 3 A cylindrical battery is shown. Figure 4 A prismatic battery is shown, and Figure 5 and Figure 6 A pouch-type battery is shown. (See reference) Figures 3 to 6 The rechargeable battery 100 may include an electrode assembly 40 and a housing 50. The electrode assembly 40 includes a separator 30 between a positive electrode 10 and a negative electrode 20, and is housed within the housing 50. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte solution. Figure 3 As shown, the rechargeable battery 100 may include a sealing member 60 of the sealed housing 50. Figure 4 As shown, the rechargeable battery 100 may include a positive electrode lead connector 11, a positive electrode terminal 12 connected to the positive electrode lead connector 11, a negative electrode lead connector 21, and a negative electrode terminal 22 connected to the negative electrode lead connector 21. Figure 5 and Figure 6As shown, the rechargeable battery 100 may include electrode terminals 70, such as a positive electrode terminal 71 and a negative electrode terminal 72. The electrode terminals 70 / 71 / 72 form an electrical path for guiding current formed in the electrode assembly 40 to the outside of the rechargeable battery 100.

[0087] The rechargeable battery according to the example embodiment can be used in, for example, automobiles, mobile phones and / or various types of electronic devices.

[0088] In the following description, examples and comparative examples of the present invention will be presented. However, the following examples are merely exemplary, and this disclosure is not limited thereto.

[0089] Example 1 An electrospinning solution containing 15 wt% polyacrylonitrile was prepared by dissolving polyacrylonitrile in dimethylacetamide solvent.

[0090] The prepared electrospinning solution is loaded into an electrospinning apparatus and electrospinned on a substrate to form a layer containing a polyacrylonitrile nanofiber network on the substrate. The electrospinning process is carried out by the following method.

[0091] A nozzle assembly comprising 52 tips with an aperture of 25G and a collecting roller were positioned 15 cm apart. An electrospinning solution was added to the tips, and a voltage of 40 kV to 50 kV was applied. Electrospinning was then performed at 26°C and 50% relative humidity. The collecting roller speed was 1 m / min to 3 m / min, and the solids content in the electrospinning solution discharged from the tips was set to 150 μL / min. Electrospinning was performed by circulating compressed air at a pressure of 0.1 MPa. After electrospinning, the solution was dried with hot air at 90°C. A 5 μm thick layer containing a polyacrylonitrile nanofiber network was formed by electrospinning.

[0092] The layer containing the polyacrylonitrile nanofiber network was separated from the substrate, and the layer containing the polyacrylonitrile nanofiber network was heat-treated at 2800°C for 1 hour under a nitrogen atmosphere to form a layer containing a graphite nanofiber network with an average diameter of 400 nm.

[0093] The layer containing the graphite nanofiber network is formed as a felt.

[0094] SEM images of the surface of a layer containing a graphite nanofiber network were captured and are shown below. Figure 7 As can be seen, this layer contains entangled graphite nanofibers and is formed in a felt-like manner.

[0095] TEM images of layers containing graphite nanofiber networks were captured and shown. Figure 8 In the middle. For example Figure 8As shown, in the SAED pattern, the ring pattern is shown together with the spots, indicating the presence of the (002) crystal plane of graphite. Additionally, as... Figure 8 As shown, the stacked structure of graphite planes was confirmed, and the (d002) interplanar spacing of 3.35 Å was verified. Therefore, it can be seen that graphitization via heat treatment resulted in the formation of graphite nanofibers.

[0096] Example 2 Except that the heat treatment temperature in Example 1 is changed to 3000°C, the layer containing the graphite nanofiber network is formed in the same manner as in Example 1.

[0097] Comparison Example 1 Except that the heat treatment temperature in Example 1 is changed to 1000°C, the layer containing the nanofiber network is formed in the same manner as in Example 1.

[0098] The following physical properties are evaluated for the nanofiber-containing layers formed in the example and comparative examples.

[0099] Specific surface area (unit: m²) 2 / g) The BET specific surface area was measured using a Macsorb HM Model-1208 (MOUNTECH).

[0100] Porosity (unit: %) SEM images of the layer containing graphite nanofibers were captured and analyzed using ImageJ software.

[0101] Elemental analysis (unit: wt%) The carbon content was obtained by performing EDS (energy-dispersive X-ray spectroscopy) elemental analysis on the layer containing graphite nanofibers and by performing surface mapping elemental analysis on individual fibers.

[0102] XRD crystallography The crystallinity of nanofibers in layers containing graphite nanofibers was analyzed using an XRD analyzer (such as a D / MAX-2500 analyzer) at a scan rate of 0.2° / min within a 2θ range of 10° to 90°. The results are shown in... Figure 9 In the middle. For example Figure 9 As shown, the graphite nanofibers of Example 1 exhibit carbon peaks.

[0103] Charge and discharge capacity and cycle life A half-cell rechargeable lithium battery is fabricated using individual layers of a graphite nanofiber network formed in the example and comparative examples as the working electrode (negative electrode) and lithium metal as the counter electrode.

[0104] Electrode assemblies were fabricated by assembling counter electrodes, negative electrodes, and a 16 μm thick polyethylene separator, followed by injection of electrolyte to create a cylindrical rechargeable lithium battery. The electrolyte was prepared by dissolving 1.5 M LiPF6 in a non-aqueous organic solvent containing carbonate solvents (e.g., ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC)) in a volume ratio of 20:40:40 (EC:EMC:DMC).

[0105] The room temperature charge-discharge characteristics of a half-cell rechargeable lithium-ion battery were evaluated. To this end, the rechargeable lithium-ion battery was subjected to charge and discharge cycles at 25°C under the conditions of 0.2C charging (CC / CV, 4.2V, 0.01C cutoff) / 0.5C discharging (CC, 2.8V cutoff). Cycle life was calculated by multiplying (200th cycle discharge capacity / 1st cycle discharge capacity) by 100%.

[0106] The evaluation results are shown in Table 1.

[0107] Table 1

[0108] As shown in Table 1, the negative electrodes for rechargeable batteries of Examples 1 and 2 provide long cycle life. However, also as shown in Table 1, the negative electrode for rechargeable batteries of the comparative examples exhibits poor performance compared to the negative electrodes of the examples.

[0109] Although preferred embodiments of the present disclosure have been described above, the present disclosure is not limited thereto, and various modifications falling within the scope of the present disclosure are possible.

Claims

1. A negative electrode for a rechargeable battery, said negative electrode comprising a layer including a network of graphite nanofibers, in, The layer has a 7m 2 / g or greater specific surface area and 75% to 90% porosity.

2. The negative electrode according to claim 1, wherein, The porosity is 80% to 90%.

3. The negative electrode according to claim 1, wherein, The porosity is 85% to 90%.

4. The negative electrode according to claim 1, wherein, The average diameter of the graphite nanofibers is 300 nm to 500 nm.

5. The negative electrode according to claim 1, wherein, The layer containing the graphite nanofiber network is a felt.

6. The negative electrode according to claim 1, wherein, The layer containing the graphite nanofiber network comprises 99.5 wt% or more of the graphite nanofibers.

7. The negative electrode according to claim 1, wherein, The graphite nanofibers in the network are connected to adjacent graphite nanofibers via carbon-carbon bonds.

8. The negative electrode according to claim 1, wherein, The negative electrode for the rechargeable battery does not include a current collector.

9. The negative electrode according to claim 1, wherein, The layer is based on 100 wt% of the graphite nanofiber network, and the graphite nanofiber network includes 1 wt% or less of one or more of a binder and a conductive material.

10. The negative electrode according to claim 1, wherein, The graphite nanofibers exhibit an (002) crystal plane with an XRD peak at 2θ = 26° in XRD analysis.

11. The negative electrode according to claim 1, wherein, The graphite nanofibers have a (002) interplanar spacing of 3.35 Å.

12. A rechargeable battery, said rechargeable battery comprising: The negative electrode for a rechargeable battery according to any one of claims 1 to 11; as well as Positive electrode.

13. The rechargeable battery according to claim 12, wherein, The positive electrode comprises a nickel-based active material, which has a nickel content of 80 mol% or more relative to 100 mol% of metals other than lithium in the nickel-based active material.

14. The rechargeable battery according to claim 12, further comprising an electrolyte comprising a non-aqueous organic solvent, the non-aqueous organic solvent comprising a mixture of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate, wherein the volume ratio of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate is 10 to 30: 20 to 50: 20 to 50.

Citation Information

Patent Citations

  • Manufacture Method of Orange Wine Using Shine-muscat

    KR1020250055067A